G349 Managing children with significant congenital cardiac disease outside tertiary cardiac centres: a three-year retrospective study. (7th April 2014) - Chee, YH; Kelsall, AW; Yates, R; Singh, Y
Abstract : Background: It has been "standard practice" for antenatal and postnatally diagnosed significant congenital heart disease (CHD) to be managed at tertiary cardiac centres (CC). Capacity constraints in the tertiary cardiac centres have called for a change in practice. With the appointment of Paediatricians with Expertise in Cardiology (PEC) working closely with paediatric cardiologists in networks, it is possible to keep selected children in non-cardiac tertiary neonatal and paediatric intensive care units. Patients would be transferred electively to the CC when specialist intervention was indicated. Aims: The aims of this study were to review outcome of children with significant CHD initially managed outside tertiary cardiac centres. Methodology: Patients were identified from neonatal and paediatric databases. A 3-year retrospective review (2011–2013) of patients' records was performed. Patients with patent ductus arteriosus, simple atrial septal defects or minor valvular problems were excluded from the study. Results: 40 patients with significant CHD were identified. Twenty-eight (70%) were managed on NICU and twelve (30%) on PICU. Of the neonatal cases: 17(61%) were diagnosed antenatally. Of these, fifteen had significant CHD, including tetralogy of Fallot (n=3), DORV (n = 3), aortic arch anomalies (n = 3), pulmonary vessel anomalies (n = 2), cardiomyopathies (n = 1) and hypoplastic left heart (n = 1). Two were fetal SVTs complicated with effusions. CHD was diagnosed postnatally in 11 infants, including transposition of great arteries (n = 3), severe pulmonary stenoses (n=2) and coarctation of aorta (n = 1). The mean length of stay for NICU patients was 13.7 (range 172) days; thirteen (46%) were transferred for cardiac intervention. Five (38%) were operated within their first week of transfer. The mean length of stay for PICU patients was 10.6 (range 1–61) days with 100% survival outcome. Four (33%) were transferred for specialist intervention. Conclusion: Neonatal and paediatric intensive care units outside tertiary cardiac centres can play an important role in initial stabilisation and management of children with significant CHDs prior to cardiac intervention. We demonstrated the ability of a non-tertiary cardiac centre in managing these children with a consistent and positive outcome, when care was delivered in close collaboration with a tertiary paediatric cardiac centre.